Social Presence in Live Streaming: A Catalyst for Impulsive Purchases - Sawarsa, Bartolomeus Wahyu; Riza, Fahrul; Salim, Steven Jonathan (Dinasti International Journal of Digital Business Management, 2023)
The aim of this research is to examine impulse buying in society, particularly focusing on the significant role of social presence within live streaming platforms in influencing impulsive purchases. This study utilizes the Stimulus-Organism-Response (SOR) model to investigate the causal relationship between the independent variable—social presence of live streaming platforms—and the dependent variable—impulsive buying behavior. Employing an explanatory research design, this study aims to establish the relationship between these variables. Data collection involved quantitative analysis using Smart PLS 3.9.2 Software. A total of 166 respondents were selected based on specific criteria relevant to the study's objectives. The findings indicate a positive and significant impact of the social presence of live streaming platforms on consumer trust and the flow state. Furthermore, consumer trust exhibits a substantial and positive influence on the flow state. Both consumer trust and the flow state significantly and positively affect impulsive buying behavior.